The Influence of Fly Ash from Sewage Sludge on the Concrete Carbonation Course - Gabriela Rutkowska; Mariusz Żółtowski; Konstantin Rusakov; Katarzyna Pawluk; Joanna Andrzejak; Bogdan Żółtowski (Buildings, 2023)
CO2 emission limits introduced by the European Union are encouraging works on new-generation materials with reduced clinker content. Currently, fumed silica from hard coal combustion is used in cement and concrete technology in Europe and Poland. Its wide application depends mainly on its chemical and phase composition, especially the reactivity of pozzolanic acids and its high fineness similar to cement Many authors studied the influence of fly ashes from hard coal combustion, in accordance with PN-EN 450-1 and 450-2, on the properties of concrete, including the course of the carbonation process. There are no studies in the literature involving ashes from sewage sludge. The objective of the research is to assess the course of carbonation of concrete produced on the basis of fly ash from the thermal transformation of sewage sludge over time and to describe this phenomenon in a mathematical form. An additional objective was to analyze the physicochemical composition of sludge ash in accordance with the requirements of EN 450-1, ASTM-C618-03. In addition, this study also demonstrated the possibility of producing fly ash-modified standard concrete through the thermal treatment of sewage sludge. The average compressive strengths of Krakow gray concrete after curing for 28, 56, 90, and 365 days were 50.1 MPa, 50.6 MPa, 50.8 MPa, and 61.9 MPa, respectively. On the one hand, the additives introduced in the concrete mixture accelerate the carbonation process by shifting the carbonation front deep into the concrete and, on the other hand, create a denser microstructure In all cases, the largest increase in carbonation depth was observed up to the 56th day of the study, while the smallest increase was observed between 90 and 180 days. The diffusivity decreases and the rate of carbonation is reduced. The determined regression coefficients of hyperbolic models indicate the proper adjustment of the adopted hyperbolic model to the results of laboratory tests under accelerated carbonation conditions (R = 0.85–0.99), regardless of the content of fly ash from sewage sludge in ordinary concrete samples.